A Novel Illuminance Control Strategy for Roadway Lighting Based on Greenshields Macroscopic Traffic Model - Neveen Shlayan; Kiran Challapali; Dave Cavalcanti; Talmai Oliveira; Yong Yang (IEEE Photonics Journal, 2018)
Most street lights currently deployed have constant illumination levels or vary based on a predetermined schedule. However, with advances in lighting controls, intelligent transportation systems, and the efforts of transportation agencies at regional and national levels to better sustain and manage the transportation system by monitoring the roadway network, many different types of real-time traffic data are available; which enables the implementation of a traffic responsive outdoor light system. The International Commission on Illumination (CIE) has proposed a class-based lighting control model based on a number of roadway parameters, some of which are traffic related. However, the adaptation of the available traffic data to the existing model is not obvious. In addition, the CIE model can be improved to better reflect traffic characteristics to increase energy efficiency of the overall street lighting system. The intention of this research is to quantify the relationship between real-time traffic, and roadway lighting and to develop a control strategy based on real-time traffic data in order to reduce light energy consumption, enhance safety, and maximize throughput of the roadway. Significant energy savings were observed when the proposed control strategy was implemented in two case studies using available lighting and traffic data for Washington, DC, and Montgomery County, MD, representing urban and rural roadway networks, respectively.